Participation of physical activities during free time and the relation of the secundary traumatic stress in firefigther - Jimmy Fernando Rojas-Quirós; Jorge Salas Cabrera; Kristy Barrantes Brais (Federación Extremeña de Balonmano; University of Extremadura, 2015)
The purpose was to analyze the relationship between the participation of physical activity (PA) and the psychological processes of Secondary Traumatic Stress (STS) on firefighters. Levels of participation in PA during free time and prevalence of STS were measured in a convenience sample of 56 firefighters using the Secondary Traumatic Stress Questionnaire and the Global Physical Activity Questionnaire. Findings show that 80.3% of the firefighters report moderate and vigorous free time-PA levels, investing an average of 2662.86 MET-min/week. Free time-PA levels show positive and significant correlations with the Secondary Trauma/Symptoms subscale of STS (r=.324, sig. .015), which is the factor with higher prevalence (32.1%), followed by Shattered Assumptions with 17.9%. In conclusion, firefighters with higher levels of free time-PA tend to report higher scores of ETS, specifically regarding to Secondary Trauma/Symptoms.